2007
DOI: 10.1093/humrep/dem075
|View full text |Cite
|
Sign up to set email alerts
|

Highly purified FSH is as efficacious as recombinant FSH for ovulation induction in women with WHO Group II anovulatory infertility: a randomized controlled non-inferiority trial

Abstract: This urinary HP-FSH preparation is non-inferior compared with a rFSH preparation with respect to ovulation rate in anovulatory WHO Group II women failing to ovulate or conceive on clomiphene citrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 24 publications
2
51
0
2
Order By: Relevance
“…The biosimilarity between Bemfola (Finox AG, Switzerland) and Gonal-f (Merck Serono, Germany) for various efficacy parameters was coupled with a safety profile that is consistent with other studies in this clinical setting (Recombinant Human FSH Study Group, 1995;Bergh et al, 1997;Frydman et al, 2000;Schats et al, 2000;Balen et al, 2007). In addition, Bemfola (Finox AG, Switzerland) treatment did not result in increased immunogenicity compared with the reference comparator Gonal-f (Merck Serono, Germany).…”
Section: P-valuesupporting
confidence: 73%
“…The biosimilarity between Bemfola (Finox AG, Switzerland) and Gonal-f (Merck Serono, Germany) for various efficacy parameters was coupled with a safety profile that is consistent with other studies in this clinical setting (Recombinant Human FSH Study Group, 1995;Bergh et al, 1997;Frydman et al, 2000;Schats et al, 2000;Balen et al, 2007). In addition, Bemfola (Finox AG, Switzerland) treatment did not result in increased immunogenicity compared with the reference comparator Gonal-f (Merck Serono, Germany).…”
Section: P-valuesupporting
confidence: 73%
“…The ovulation rate was 85.2% with HP-FSH and 90.9% with rFSH. No differences were noted between groups in number of follicles ≥12mm, ≥15mm or ≥18mm, mono-follicular development, pregnancy rates, endometrial thickness, number of ovarian stimulation syndrome cases (25). …”
Section: Discussionmentioning
confidence: 88%
“…In a recent Cochrane review of four randomized trials comparing rFSH versus urinary FSH for ovulation induction for women with polycystic ovarian syndrome, it was concluded that there was not enough evidence to recommend one of these products over the other (4). In addition, a recent randomized trial of HP-hFSH versus rFSH found that HP-hFSH was noninferior compared with rFSH with respect to ovulation rate in anovulatory World Health Organization Group II of women who failed to ovulate or conceive on clomiphene citrate (5). Although a recent randomized study of rFSH and urinary products suggested a better outcome with rFSH in intrauterine insemination cycles for unexplained infertility, the urinary comparators used were older products no longer used in the United States (6).…”
Section: Discussionmentioning
confidence: 99%